Pengaruh Indeks Harga Konsumen Terhadap Inflasi di Indonesia: The Effect of the Consumer Price Index on Inflation in Indonesia - Sabela Almahdiyina Kamila; Rohmad Abidin (UIN K.H. Abdurrahman Wahid Pekalongan, 2022)
Inflation is a problem that is of concern to governments in various countries around the world. Inflation is an increase in the overall price of goods and services and occurs from time to time. One of the indicators used to assess a country's inflation rate is the consumer price index. The consumer price index can provide data on the evolution of the prices of goods and services paid by consumers. This study discusses the effect of the consumer price index on the inflation rate in Indonesia. The purpose of this study is to determine whether the consumer price index can affect the inflation rate in Indonesia. This research is a type of descriptive quantitative research where the data used is secondary data taken from the official website of the Central Statistics Agency. The population of this study is the consumer price index and the inflation rate in Indonesia from 2019 to 2021. The researcher uses a saturated sample as a sampling technique. The data analysis technique used in this research is using a linear regression analysis approach, including the classical assumption test (normality test, heteroscedasticity test, and autokorelation test), and t test. The result of this research is that the consumer price index has no significant and positive effect on the dependent variable, namely inflation. The consumer price index has an effect of 2% on inflation. While 98% is influenced by other variables not examined in this study.